Multilingual Education in Southwest Sumba: Current Practice, Teachers’ Attitudes and Beliefs - Ekarina; Kristoforus Dowa Bili; Murniati Agustian; Tia Xenia; Yanti (Linguistik Indonesia, 2025)
This study investigates the current multilingual practice situation at Southwest Sumba schools, as well as the beliefs and attitudes of the teachers on a multitude of issues related to multilingualism and multilingual education. The methodology used was a questionnaire on issues related to (i) the need of multilingual education, (ii) students’ mother tongues, and (iii) literacy. The data was collected from four primary schools in Southwest Sumba, two of which are located in Kodhi speaking areas, while the other two are located in Wewewa speaking areas. Results from the data analysis revealed that the Indonesian centered curriculum, lessons, materials and assessment system have a negative impact on students’ academic achievement. However, teachers and schools are currently not equipped to respond to the students’ needs of a multilingual education program. Despite that, the surveyed teachers have very positive attitudes and beliefs towards multilingual education not only as a way to improve students’ academic performance, but also as a means to preserve the students’ local language.